High-Throughput Sequencing to Investigate lncRNA-circRNA-miRNA-mRNA Networks Underlying the Effects of Beta-Amyloid Peptide and Senescence on Astrocytes - Deng, Yuxin; Song, Hui; Xiao, Yan; Zhao, Yi; Chu, Liangzao; Ding, Jiuyang; Shen, Xiangchun; Qi, Xiaolan (Frontiers in Genetics, 2022)
Astrocytes are widely distributed in the central nervous system and play an essential role in the function of neuronal cells. Associations between astrocytes and Alzheimer’s disease (AD) have been noted, and recent work has implicated circular RNA (circRNA) and long non-coding RNA (lncRNA) in the development of AD. However, few reports have investigated which lncRNA and circRNA are involved in the influence of amyloid beta (Aβ) and senescence on astrocytes. This study therefore examines changes at the transcriptome level to explore the effects of Aβ and senescence on astrocytes. Primary cultured astrocytes were treated with Aβ and cultured for 90 days in vitro, and high-throughput sequencing was performed to identify differentially expressed RNAs. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses revealed that differentially expressed genes were associated with the focal adhesion signaling pathway, extracellular matrix receptor signaling pathway, and the extracellular matrix. The protein–protein interaction network was then constructed, and 103 hub genes were screened out; most of these were strongly associated with the expression of the extracellular matrix, extracellular matrix receptor signaling pathway, and focal adhesion. Two competing endogenous RNA networks were constructed based on the selected hub gene and differential RNAs, and we identified multiple competing endogenous RNA regulatory axes that were involved in the effects of Aβ and senescence on astrocytes. This is the first study to explore the molecular regulation mechanism of Aβ and senescence on primary astrocytes from the perspective of the whole transcriptome. In uncovering the signaling pathways and biological processes involved in the effects of Aβ and senescence on astrocytes, this work provides novel insights into the pathogenesis of AD at the level of competing endogenous RNA network regulation.